Design and implementation of a MEMS piezoelectric sensor array for patient specific instrumentation used for total ankle replacement - Bedoya-Serrano, Marco (Instituto Tecnológico de Costa Rica, 2017)
For several decades, research has been conducted for Total Ankle Replacement (TAR) to be established as the optimal surgical treatment for diseased or degenerative ankle joints. Few reports exist regarding patient specific instrumentation for TAR and to the author knowledge, there is no work related to sensing technology designed for patient specific instrumentation in Total Ankle Replacement. This research analyses how piezoelectric, patient specific instrumentation and micro-electro-mechanical system (MEMS) technologies can be combined to design a thin flexible pressure map sensor for Total Ankle Replacement application. More specifically, the sensor design claims to provide information on how the patient specific instrument fits onto the bone surface when performing a Total Ankle Replacement. Finite Element Analysis is used (FEA) to verify design calculations and afterwards, fabrication and assembly of the sensor are followed. A custom made data acquisition system was designed and built to read the output of the sensor. Prototype successful implementation was achieved through experimental setup, where several test cases scenarios were recorded. In particular, sensor voltage output data ranges from approximately 128 mV to 310 mV, translated in mechanical deformation from approximately 59 MPa to 161 MPa, while theoretical mechanical deformation ranged from 50 MPa to 150 MPa according to calculations and FEA results.
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017.
Keywords: Tecnología; Instrumentación; Prototipos; Sensores